What second-language speakers can tell us about pragmatic processing - Khorsheed, Ahmed; Md. Rashid, Sabariah; Nimehchisalem, Vahid; Geok Imm, Lee; Price, Jessica; Ronderos, Camilo R. (PLOS ONE, 2022)
Upon hearing the phrase Some cats meow, a listener might pragmatically infer that ‘Some but not all cats meow’. This is known as a scalar implicature and it often arises when a speaker produces a weak linguistic expression instead of a stronger one. Several L2 studies claim that pragmatic inferences are generated by default and their comprehension presents no challenges to L2 learners. However, the evidence obtained from these studies largely stems from offline-based tasks that provide limited information about how scalar implicatures are processed. This study investigated scalar implicature processing among L2 speakers of English and the degree to which differences in L2 proficiency and Theory of Mind abilities would modulate pragmatic responding. The experiment used an online sentence verification paradigm that required participants to judge, among multiple control items, the veracity of under-informative sentences, such as Some cats are mammals, and to respond as quickly as possible. A true response to this item is indicative of a logical some and perhaps all reading and a false response to a pragmatic some but not all reading. Our results showed evidence that scalar inferences are not generated by default. The answer linked to the pragmatic reading some but not all took significantly longer to make relative to the answer that relies on the logical interpretation some and perhaps all. This processing slowdown was also significantly larger among participants with lower English proficiency. Further exploratory analyses of participants’ Theory of Mind, as measured by the Social Skill subscale in the Autism Spectrum Quotient, revealed that socially inclined participants are more likely than the socially disinclined to derive a scalar inference. These results together provide new empirical insights into how L2 learners process scalar implicatures and thus implications for processing theories in experimental pragmatics and second language acquisition.